Disability risk, disability insurance and life cycle behavior - Hamish Low; Luigi Pistaferri (Institute for Fiscal Studies (IFS), 2010)
This paper provides a life-cycle framework for weighing up the insurance value of disability benefi ts against the incentive cost. Within this framework, we estimate the life-cycle risks that individuals face in the US, as well as the parameters governing the disability insurance program, using indirect inference and longitudinal data on consumption, disability status, disability insurance receipt, and wages. We use our estimates to characterize the effectiveness of the disability insurance program and to consider the e ffect on welfare and behaviour of policy reform. High levels of false rejections associated with the screening process imply welfare increases as the program becomes less strict, despite the worsening incentives that this implies. Incentives for false applications are reduced by reducing generosity and increasing reassessments and these improve welfare, despite the worse insurance implied.
Keywords: D91; H53; H55; J26; 330; Disability; social security; savings behavior; wage risk; Erwerbsunfähigkeit; Risiko; Unfallversicherung; Erwerbsunfähigkeitsrente; Lebenszyklus; Wohlfahrtseffekt